Performance and Environmental Sustainability of Cash Crop Production in Pampas Region, Argentina - Rótolo, Gloria C.; Montico, Sergio; Francis, Charles A.; Ulgiati, Sergio (Journal of Environmental Accounting and Management, 2026)
The Pampas region contributes 80% of the total national production of soya, wheat and maize in Argentina, characterized by large grain exports and internal consumption. Today the area allocated to these crops is driven by short-term economic opportunities, creating a tension between people with vested economic interests and those more concerned about the benefits provided by preserving natural capital and ecosystem services. The objectives of this study were toanalyze resource use, environmental impact, and sustainability of annual crop production in the northern Pampas regions and promote discussion of management strategies and production goals. SUMMA (Sustainability Multimethod Multiscale Assessment), an approach that integrates material demand, energy use, emergy and emissions within a life cycle assessment framework, provides indicators of resource depletion, environmental impact and performance of agricultural systems. Results show a more than doubled water demand per hectare for soy and three times higher for maize and wheat in 2009 compared to 1986, while abiotic material demand per ha decreased down to 10% of the reference year values. On a per gram basis, 2-5 g water were needed in 2009 per gram of product dry matter, with higher demand for wheat and lower for maize. Energy demand decreased by about 60% for soy on per hectare basis, while increased for maize and wheat. About 460 kg CO2 equiv/ha and 3.2 kg SO2equiv/ha were released in 2009 by soybean and up to three times more by maize and wheat, translating into 0.1-0.3 g CO2 equiv/g d.m. of product (with maize performing better and wheat worse). Finally, emergy indicators show an unbalance between use of resources that are free renewable and locally available and resources that are nonrenewable and purchased from outside the system. This unbalance cannot be disregarded, being a key aspect of sustainability.